2001
DOI: 10.1111/j.1752-1688.2001.tb05529.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF AN OPTIMAL SAMPLING STRATEGY FOR A CONSTRUCTED WETLAND1

Abstract: The objective of this investigation was to determine the effect of sampling frequency and sampling type on estimates of monthly nutrient loads and flow‐weighted nutrient concentrations in a constructed wetland. Phosphorus and nitrogen loads and concentrations entering and leaving a subtropical wetland (the Everglades Nutrient Removal Project, ENRP) were calculated on the basis of three sampling frequencies. The first frequency included weekly composite samples (three daily samples composited for one week) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The investigation by Moustafa and Havens (2001) determined the effect of sampling frequency and sampling type on estimates of monthly nutrient loads and flow-weighted nutrient concentrations in a constructed wetland. The results showed that bi-weekly composite sampling could be used to monitor nutrient concentrations and loads discharged from larger-scale Everglades Stormwater Treatment Areas (STAs) now under construction.…”
Section: Testing For Chemical Pollution and Pollution Tracersmentioning
confidence: 99%
“…The investigation by Moustafa and Havens (2001) determined the effect of sampling frequency and sampling type on estimates of monthly nutrient loads and flow-weighted nutrient concentrations in a constructed wetland. The results showed that bi-weekly composite sampling could be used to monitor nutrient concentrations and loads discharged from larger-scale Everglades Stormwater Treatment Areas (STAs) now under construction.…”
Section: Testing For Chemical Pollution and Pollution Tracersmentioning
confidence: 99%